The complete chloroplast genome sequence of Borago officinalis Linn. (Boraginaceae) and its phylogenetic analysis. Issue 2 (2nd April 2020) - Guo, Xu; Wang, Xinkun; Wang, Qing; Liu, Chao; Zhang, Ruirui; Cheng, Anwei; Sun, Jinyue
Abstract: Borago officinalis is a kind of vegetable and traditional medicinal herb in the Mediterranean region, and now it has spread many areas around the world. In this study, we sequenced a complete chloroplast (cp) genome sequence of B. officinalis to investigate its phylogenetic relationship with other species. The whole cp genome of B. officinalis is 149, 835 bp in length with 37.82% overall GC content, including a large single-copy (LSC) region of 78, 840 bp and a small single-copy (SSC) region of 16, 967 bp, which are separated by a pair of inverted repeats (IRs) of 27, 014 bp. The cp genome contains 110 genes, including 76 protein-coding genes, 30 tRNA genes, and 4 rRNA genes. The phylogenetic analysis based on cp genome sequences showed that B. officinalis is closely related to Antirhea chinensis, Mitragyna speciosa and Neolamarckia cadamba.